CONTRIBUTIONS TO THE STUDY OF BAGRID FISHES (SILUROIDEA : BAGRIDAE). 3.A SYSTEMATIC ACCOUNT OF THE JAPANESE, CHINESE, MALAYAN AND INDONESIAN GENERA - K C JAYARAM (Research Center for Biology, 1968)
ABSTRACT NOT AVAILABLE